Three months prognosis of transient ischemic attack (TIA) in Erbil Governorate - Ahmed, Abdullah Faqiyzadin (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: A transient ischemic attack is a brief episode of neurological dysfunction resulting from focal cerebral ischemia not associated with permanent cerebral infarction. Transient ischemic attack carries a substantial short-term risk of stroke, hospitalization for cardiovascular events, and death. We aimed to evaluate prognosis of transient ischemic attack within three months follow up period, and identifying the predicting factors. Methods: Thirty patients with transient ischemic attack were evaluated and followed up for 3 months to identify their prognosis. ABCD2 score was used for risk stratification in index and follow up transient ischemic attack patients.Results: Within three months of follow up, 10% of patients developed transient ischemic attack and stroke each. There was an association between increasing age and increasing risk of index transient ischemic attack. Hypertension was the highest risk factors for index transient ischemic attack.Conclusion: Despite standard preventive medications, some patients will still have events later on.